Alg_Complete

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ng with polynomials works the same way. So in this case we have, ( 2 x + 6) 2 = ( 2 x + 6 )( 2 x + 6 ) = 4 x 2 + 12 x + 12 x + 36 = 4 x 2 + 24 x + 36 [Return to Problems] (c) (1 - 7 x ) 2 This one is nearly identical to the previous part. (1 - 7 x ) 2 = (1 - 7 x )(1 - 7 x ) = 1 - 7 x - 7 x + 49 x 2 = 1 - 14 x + 49 x 2 [Return to Problems] © 2007 Paul Dawkins 29 http://tutorial.math.lamar.edu/terms.aspx College Algebra (d) 4 ( x + 3) 2 This part is here to remind us that we need to be careful with coefficients. When we’ve got a coefficient we MUST do the exponentiation first and then multiply the coefficient. 4 ( x + 3) = 4 ( x + 3)( x + 3) = 4 ( x 2 + 6 x + 9 ) = 4 x 2 + 24 x + 36 2 You can only multiply a coefficient through a set of parenthesis if there is an exponent of “1” on the parenthesis. If there is any other exponent then you CAN’T multiply the coefficient through the parenthesis. Just to illustrate the point. 4 ( x + 3) ¹ ( 4 x + 12 ) = ( 4 x + 12 )( 4 x + 12 ) = 16...
View Full Document

This note was uploaded on 06/06/2012 for the course ICT 4 taught by Professor Mrvinh during the Spring '12 term at Hanoi University of Technology.

Ask a homework question - tutors are online